Public Assistance, Drug Testing, and the Law: The Limits of Population-Based Legal Analysis - Player, Candice T. (American journal of law & medicine, 2014)
In Populations, Public Health and the Law, legal scholar Wendy Parmet urges courts to embrace population-based legal analysis, a public health inspired approach to legal reasoning. Parmet contends that population-based legal analysis offers a way to analyze legal issues—not unlike law and economics—as well as a set of values from which to critique contemporary legal discourse. Population-based analysis has been warmly embraced by the health law community as a bold new way of analyzing legal issues. Still, population-based analysis is not without its problems. At times, Parmet claims too much territory for the population perspective. Moreover, Parmet urges courts to recognize population health as an important norm in legal reasoning. What should we do when the insights of public health and conventional legal reasoning conflict? Still in its infancy, population-based analysis offers little in the way of answers to these questions. This Article applies population-based legal analysis to the constitutional problems that arise when states condition public assistance benefits on passing a drug test, thereby highlighting the strengths of the population perspective and exposing its weaknesses